Moderating Role Competitive Advantage on Effect of Sustainability Disclosure to Financial Performance - Marchel Marchel; Elyzabet Indrawati Marpaung (Politeknik Ganesha Medan, 2026)
The purpose of this research is to analyze the moderating effect of competitive advantage on the effect of sustainability disclosure on corporate financial performance. Sustainability disclosure is currently one of the important aspects of corporate strategy, especially in an effort to create long-term value and strengthen the company's reputation in the eyes of stakeholders. This study uses a quantitative approach by utilizing SPSS version 26 software as an analytical tool. The hypothesized hypothesis was tested using the linear regression test and moderated regression analysis to ascertain the degree of influence between the moderating and independent variables. The results showed that sustainability disclosure has a positive effect on financial performance. This finding supports stakeholder theory and signaling theory. In addition, competitive advantage is also proven to strengthen the effect of sustainability disclosure on financial performance. Companies with a significant competitive edge can make better use of sustainability disclosures. According to the research's practical consequences, businesses must actively develop their competitive edge in addition to focusing on thorough sustainability reporting. Adding a moderating variable, competitive advantage, and measuring the independent variable using the Sustainability Reporting Disclosure Index in compliance with POJK No. 51/POJK.03/2017 and SEOJK No. 16/SEOJK.04/2021 are what make this study novelty.